2006
DOI: 10.1098/rstb.2006.1829
|View full text |Cite
|
Sign up to set email alerts
|

Managing future Gulf War Syndromes: international lessons and new models of care

Abstract: After the 1991 Gulf War, veterans of the conflict from the United States, United Kingdom, Canada, Australia and other nations described chronic idiopathic symptoms that became popularly known as 'Gulf War Syndrome'. Nearly 15 years later, some 250 million dollars in United States medical research has failed to confirm a novel war-related syndrome and controversy over the existence and causes of idiopathic physical symptoms has persisted. Wartime exposures implicated as possible causes of subsequent symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 98 publications
(115 reference statements)
1
18
0
2
Order By: Relevance
“…8 Th e potential of mass screenings to stigmatize the problems that screening seeks to identify also has been noted. 28 Th e fi ndings of this report reinforce the concerns of others regarding the ability of pre-deployment health assessments to identify mental disorders that are diagnosed prior to deployment that may be medically and military operationally signifi cant during deployment.…”
supporting
confidence: 65%
“…8 Th e potential of mass screenings to stigmatize the problems that screening seeks to identify also has been noted. 28 Th e fi ndings of this report reinforce the concerns of others regarding the ability of pre-deployment health assessments to identify mental disorders that are diagnosed prior to deployment that may be medically and military operationally signifi cant during deployment.…”
supporting
confidence: 65%
“…Although the first Gulf War (GW) that resulted in the liberation of Kuwait from the Iraqi occupation ended in early 1991, the issue of post-traumatic stress disorder (PTSD) and co-morbid conditions among the veterans of that war has continued to feature prominently in the medical scientific literature, even in recent times (Engel, Hyams, & Scott, 2006;Stein et al, 2006). However, this impressive body of work has been entirely focused on PTSD among veterans of the war from the USA and other western nations.…”
Section: Introductionmentioning
confidence: 96%
“…Problems in school also have been linked to parental deployment. For example, Engel, Hyams, and Scott (2006) found significant decreases in test scores for children of deployed parents, with longer deployments associated with lower test scores. Chandra, Martin, and colleagues (2010) conducted focus groups with school personnel who reported that, for many children, parental deployment led to sadness and anger, resulting in classroom disruption and negative effects on peer relationships.…”
Section: Child Outcomesmentioning
confidence: 99%